DI-087 Restrictive allograft syndrome in lung transplantation: nintedanib as a new therapeutic strategy?. (25th February 2017) - Pluchart, H; Chanoine, S; Beaumier, L; Briault, A; Quetant, S; Pison, C; Bedouch, P
Abstract : Background: Lung transplantation is hampered by some complications, particularly acute rejection and chronic lung allograft dysfunction (CLAD), the latter including bronchiolitis obliterans syndrome (BOS) and restrictive allograft syndrome (RAS) with fibrotic process. RAS therapeutic strategy is not clearly defined, but several cases reported the use of antifibrotic agents, indicated in idiopathic pulmonary fibrosis (IPF), to treat RAS, such as pirfenidone. 1 Purpose: In this case report we relate the use of nintedanib, a new antifibrotic agent, for RAS treatment in a lung transplanted patient. Material and methods: Case report Results: A 71-year-old-man received a right lung transplant in 2009 because of IPF. In 2010, BOS stage 0-p was found, evolving to stage 1 in 2011 and leading to the introduction of montelukast and azithromycin, and extracorporeal photopheresis. Despite these therapies, the forced expiratory volume 1 (FEV1) per cent predicted decreased to 43% and dyspnoea worsened, suggesting evolution of BOS towards RAS, whose prognosis is worse. Oxygen therapy was introduced in January 2016 (1.5 L/min during exercise). In February 2016, CT showed IPF large lesions in the left lung and worse RAS fibrotic lesions in the right lung. A multidisciplinary team decided to start nintedanib 150 mg twice a day. The patient's immunosuppressive therapies (tacrolimus and everolimus) were monitored every 15 days because of potential cytochrome 3A4 induction of nintedanib. During nintedanib treatment, oxygen debit was 1 L/min during exercise and FEV1% predicted was 47%, suggesting clinical improvement. Nintedanib was stopped in August 2016 because of persistence of digestive intolerance. Conclusion: Our clinical case suggests a potential clinical benefit of nintedanib in the treatment of RAS. To our knowledge, this is the first case reporting the use of nintedanib, a tyrosine kinase inhibitor targeting platelet derived growth factor receptors and fibroblast growth factor receptor, to treat RAS. Further studies have to be conducted to assess the place of antifibrotic agents in RAS therapeutic management. References and/or acknowledgements: 1. Vos R, Verleden SE, Ruttens D, et al. Pirfenidone: A potential new therapy for restrictive allograft syndrome? Am J Transplant Off J Am Soc Transplant Am Soc Transpl Surg 2013;13:3035–40. No conflict of interest